Psychometric properties of Mental Health Scale: An Item Response Theory Approach - Ramadhan Dwi Marvianto (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Indonesia Family Life Survey (IFLS) the fifth wave used the Centre for Epidemiological Studies Scale (CES-D10) to measure mental health state, which was depressive symptoms construct. It was primarily used in some studies regarding depressive symptoms. However, there was no specific validation research in the Indonesian context. Thus, this study aimed to (1) investigate the item quality of depressive symptom measurement from IFLS fifth wave, (2) measurement precision of this scale, and (3) the measurement invariance based on gender using the IRT approach. This study used data from ILFS-5 in the KP (